2022
DOI: 10.1186/s13045-022-01307-2
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping the systemic tumor immune environment (STIE) and tumor immune microenvironment (TIME) to enhance immunotherapy efficacy in solid tumors

Abstract: The development of combination immunotherapy based on the mediation of regulatory mechanisms of the tumor immune microenvironment (TIME) is promising. However, a deep understanding of tumor immunology must involve the systemic tumor immune environment (STIE) which was merely illustrated previously. Here, we aim to review recent advances in single-cell transcriptomics and spatial transcriptomics for the studies of STIE, TIME, and their interactions, which may reveal heterogeneity in immunotherapy responses as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 274 publications
(221 reference statements)
1
58
0
Order By: Relevance
“…Tumor-associated macrophages (TAMs) in the tumor microenvironment are heterogeneous subsets, including M1 antitumor and M2 tumor-promoting phenotypes. TAMs primarily exert M2-like tumor-promoting effects in the TME and regulate various malignant effects, such as angiogenesis, immunosuppression, and tumor metastasis [ 49 , 50 ]. Prior work has reported that each of the M1 and M2 macrophages are produced by M0 is a quiescent state of macrophages with no particular role until they become polarized [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated macrophages (TAMs) in the tumor microenvironment are heterogeneous subsets, including M1 antitumor and M2 tumor-promoting phenotypes. TAMs primarily exert M2-like tumor-promoting effects in the TME and regulate various malignant effects, such as angiogenesis, immunosuppression, and tumor metastasis [ 49 , 50 ]. Prior work has reported that each of the M1 and M2 macrophages are produced by M0 is a quiescent state of macrophages with no particular role until they become polarized [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this increasing use, there is still a lack of biomarkers with predictive value for therapy response ( 1 ). Beyond blocking local immunosuppression, IT success is achieved by systemic antitumor immunity, relying on the functionality and composition of the individual immune system ( 5 ). Therefore, we developed scores based on the individual immune signature of the patient’s peripheral blood and investigated their predictive value for therapy success of IT.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral immune cells augment, sustain, and reactivate local IT effects by interaction with the tumor microenvironment. For example, circulating CD8 + T cells are assumed to migrate into the tumor microenvironment enhancing local antitumor immunity ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor-associated macrophages (TAMs) in the tumor microenvironment are heterogeneous subsets, including M1 antitumor and M2 tumor-promoting phenotypes. TAMs primarily exert M2-like tumor-promoting effects in the TME and regulate various malignant effects, such as angiogenesis, immunosuppression, and tumor metastasis (33,34). Prior work has reported that each of M1 and M2 macrophages are produced by M0 is a quiescent state of macrophages with no particular role until they become polarized (35).…”
Section: Discussionmentioning
confidence: 99%